1998
DOI: 10.1182/blood.v91.8.3011.3011_3011_3016
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of the Soluble Form of the CD30 Molecule Identifies Patients With Hodgkin's Disease at High Risk of Unfavorable Outcome

Abstract: Preliminary reports suggested a prognostic significance for serum levels of soluble CD30 (sCD30) in patients with Hodgkin's disease (HD). In this study, we investigated the prognostic impact of sCD30 concentration at diagnosis in relation to the other recognized prognostic parameters in 303 patients with HD observed in three different institutions between 1984 and 1996. sCD30 levels were correlated with stage, presence of B symptoms, and tumor burden. High sCD30 levels entailed a higher risk of poor outcome, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…From the relationship between elevation of serum sCD30 levels and clinical stage, it may be possible to identify patients with a very high or very low risk of treatment failure with standard therapy. ( 16,17 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the relationship between elevation of serum sCD30 levels and clinical stage, it may be possible to identify patients with a very high or very low risk of treatment failure with standard therapy. ( 16,17 )…”
Section: Discussionmentioning
confidence: 99%
“…In ALCL and Hodgkin's disease (HD), elevated levels of sCD30 in the sera of patients are correlated with a poor prognosis, perhaps because a high level of sCD30 reflects a high tumor burden or because sCD30 blocks the biologic effects of CD30L. ( 15–17 ) Moreover, sCD30 is detectable in the sera of ATL patients. ( 11 ) In this study, we investigated the clinical significance of the membrane type of CD30 (mCD30) expression and serum sCD30 levels in ATL.…”
mentioning
confidence: 99%
“…Supershift assay of NF-jB DNA binding complex in nuclear extracts from KM-H2 cells was also carried out. Where indicated, appropriate antibodies were added to the reaction mixture (lanes [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…13 Increased serum levels of soluble CD30 correlate with disease activity and thus bear prognostic significance in HL. 14 A later study, however, showed that CD30 was expressed not only on H/RS cells but also on a subset of large cell non-Hodgkin's lymphomas, activated lymphocytes and virus-infected lymphocytes. 15 In contrast, expression of its ligand CD30L is broader, being expressed on lymphocytes, neutrophils and eosinophils as well as activated monocytes/macrophages.…”
mentioning
confidence: 96%
“…PatientsÕ therapy and response assessment were previously described (7). sCD30 assay sCD30 levels were determined in serum samples stored at )20°C by a sandwich enzyme-linked immunosorbent assay [CD30 (Ki-1 antigen) ELI-SA, DAKO, Glostrup, Denmark], according to manufacturer instructions, as previously described (23).…”
Section: Patients Staging Therapy and Response Assessmentmentioning
confidence: 99%